Principles and orientations for media users’ ethics: contributions from the side of the Catholic Church’s Social Teaching - Fuente Cobo, María del Carmen (2017)
The paradigm shift in media and social communications is forcing us to rethinking the role and responsibility of the user. Studies on consumer ethics are relatively recent and have shown little interest in the ethical decision-making processes of media users and consumers. In the side of media ethics, the attention paid to consumers and users of the media has also been scarce. The aim of this article is to identify principles and criteria that may serve as guidelines for a media users’ ethics adapted to the current times and technologies. The reflection starts with a review of the academic literature and the principles, values and norms that can be traced in the documents of the Catholic Social Teaching (CST) on media ethics.